SCREENING OF HERBICIDES AS POST-EMERGENCE APPLICATION FOR EFFECTIVE WEED CONTROL WITHOUT AFFECTING GROWTH AND YIELD OF DIRECT SEEDED RICE PLANT - Tahir Hussain Awan; M. E. Safdar; Z. Manzoor; M. M. Ashraf (Journal of Animal and Plant Sciences, 2006)
Trials were conducted at the experimental area of Rice Research Institute, Kala Shah Kaku, Lahore during the Kharif seasons of 2000 and 2001 to find out the best strategy of chemical weed control in direct seeded Super Basmati rice (Oryza sativa L.). The experiment was laid out in randomized complete block design and replicated thrice with a net plot size of 6 x 9 m2. During each year, drill sowing was done on 10th of June after soaking seed (paddy) for 24 hrs. Different herbicide treatments kept in the experiment were Sunstar 15WG, Machete 60 EC, Puma Super 69EW, Rifit 500L, Sunstar 15WG + Puma Super 69EW and Acer 50 EC in addition to untreated control. Spray was done 22 days after sowing. Puma Super 69EW, Sunstar 15WG + Puma Super 69EW and Acer 50 EC showed maximum phytotoxicity on rice crop whereas best weed control was achieved by Sunstar 15WG and Sunstar 15WG + Puma Super 69EW herbicide treatments. In terms of paddy yield, Sunstar 15WG was proved best whereas Machete 60 EC, Sunstar 15WG + Puma Super 69EW also expressed good performance. The untreated control treatment produced the lowest (2.24 t/ha) paddy yield than all other treatments.
Keywords: Rice (Oryza Sativa); herbicides; Phytotoxicity; Yield